Narcissism in the Novels of F. Scott Fitzgerald - La, Rose Anthony Joseph (My University, 1992)
This thesis begins with the observation that, despite structural and stylistic differences, Fitzgerald's novels are thematically similar. All of his protagonists search, ultimately in vain, for some aspect of their environment that will ensure them complete and lasting happiness. From the perspective of the self psychology of Heinz Kohut each is searching for that which will compensate for his own incomplete psychological development. As a result of dysfunctional relationships early in life, they are missing psychological structure that would allow them to regulate their sense of self-esteem from within. But because they are deficient, they depend on the responses of others for self-validation. This condition leads to a heightened sense of self-consciousness; they are, more so than healthy individuals, acutely aware of and responsive to social recognition. And, because of the immensity of their psychological demands, it is ultimately the inability of the environment to respond adequately that results in their various downfalls.
Keywords: English Language and Literature; English Language and Literature